2022
DOI: 10.3390/molecules27175627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extraction Technique on the Content and Antioxidant Activity of Flavonoids from Gossypium Hirsutum linn. Flowers

Abstract: Cotton is one of the Uyghur medical materials in China and is rich in flavonoids. Flavonoids have important pharmacological effects. The yield of flavonoids in traditional extraction methods is low, which affects the development of flavonoids. Therefore, it is urgent to optimize the extraction techniques. The yield of flavonoids in cotton flowers was effectively improved by response surface methodology, and the highest yield of flavonoids reached 5.66%, and the optimal extraction process conditions were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The extract with 70% ethanol had the highest total flavonoid value (0.559 ± 0.03 mgQE/g extract). The same results are from the previous research which gave the highest total flavonoids in 70% ethanol (Suhendra et al, 2019;Rahardhian et al, 2019;Dong et al, 2022). Sucipto et al (2022) reported that optimization results of ethanol concentration showed that 70% ethanol was optimal for extracting flavonoids.…”
Section: Figure 3 Reaction For the Formation Of Complex Flavonoid-alc...supporting
confidence: 83%
“…The extract with 70% ethanol had the highest total flavonoid value (0.559 ± 0.03 mgQE/g extract). The same results are from the previous research which gave the highest total flavonoids in 70% ethanol (Suhendra et al, 2019;Rahardhian et al, 2019;Dong et al, 2022). Sucipto et al (2022) reported that optimization results of ethanol concentration showed that 70% ethanol was optimal for extracting flavonoids.…”
Section: Figure 3 Reaction For the Formation Of Complex Flavonoid-alc...supporting
confidence: 83%
“…Previous research has shown that hydroxyl radicals, which are produced naturally, are highly reactive free radicals, and that humans lack enzymes that can neutralize them [36]. Previous research established that hydroxyl radicals are highly reactive free radicals produced in the biological system, and that human ROS lacks enzymes specifically designed to neutralize them [37]. The highly high reactivity of hydroxyl (OH) radical makes its scavenging a crucial antioxidant activity, as was shown in a previous work [38].…”
Section: Antihyperlipidemic Activitymentioning
confidence: 93%
“…The antioxidant activity of TFs-Ph was evaluated by referring to some literature with minor modifications, including the scavenging activity of •OH, DPPH, •O 2− , and ABTS [29][30][31].…”
Section: Antioxidant Activity Evaluation Of Tfs-phmentioning
confidence: 99%
“…This is because an appropriate increase in temperature can accelerate the diffusion rate of molecules, and thus increase the release of bioactive substances in plant cells. But when the temperature is higher than the optimal level it would lead to the decomposition of heat-sensitive compounds such as flavonoids [29]. Thus, the best heat reflux temperature was 70 • C.…”
Section: The Influence Of Single-factor Experiments On Tfs-ph Extract...mentioning
confidence: 99%